CLINICAL SIMULATION IN NURSING TEACHING: STUDENT EXPERIENCE IN CHILE - Cabrera, Thania Andrea Aballay; Kempfer, Silvana Silveira (My University, 2020)
ABSTRACT Objective: to describe the experiences lived in clinical simulation by nursing students at the University of Magallanes, Punta Arenas, Chile, in relation to the use of clinical simulation as a learning methodology for the achievement of skills for nursing care. Method: the simulation by the students was carried out in 2017, while they attended the seventh and eighth semester of professional training. The study carried out was qualitative, exploratory descriptive, in which eight students participated using the semi-structured interview instrument applied during the second semester of 2018. Results: it was observed that the simulation experience was good and very good. It stands out that the main points of discussion for the participants were that the clinical simulation gave them tools that allowed them to acquire professional identity, empowerment of the professional role, clinical reasoning, professional practice and organization. On the other hand, it also allowed them to apply theoretical knowledge. Conclusion: although this experience allowed the students to acquire comprehensive skills, it also has the limitation that feelings of fear and anxiety emerge that may make it impossible to develop it.
Keywords: nursing students; learning; experiential learning; abilities; simulation